2021
DOI: 10.3390/nu13114159
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Fiber Intake and Incidence of Depression and Anxiety in Patients with Essential Hypertension

Abstract: (1) Background: Our previous study found that the dietary fiber supplement in patients with hypertension increased SCFA-producers, Bififidobacterium and Spirillum in the gut microbiota, which may be associated with improvement of depression and anxiety through the gut–brain axis. However, only a few studies have explored the association between dietary fiber intake (DFI) and the incidence of depression and anxiety in hypertensive patients. (2) Methods: A cross-sectional survey was conducted in one comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
2
13
0
1
Order By: Relevance
“…The quantities of dietary fiber intake in previous studies were far below the recommended doses. Liu et al [ 41 ] conducted an investigation that showed that the average daily dietary fiber intake of HTN patients was 11.25 ± 4.88 g, which is consistent with the study by Qi et al [ 42 ], who found that the average daily DF intake was 10.17 ± 4.38 g in HTN patients. In this study, HTN patients were provided with oat bran supplements, ensuring a daily consumption of DF of 21.45 ± 3.86 g/d.…”
Section: Discussionsupporting
confidence: 76%
“…The quantities of dietary fiber intake in previous studies were far below the recommended doses. Liu et al [ 41 ] conducted an investigation that showed that the average daily dietary fiber intake of HTN patients was 11.25 ± 4.88 g, which is consistent with the study by Qi et al [ 42 ], who found that the average daily DF intake was 10.17 ± 4.38 g in HTN patients. In this study, HTN patients were provided with oat bran supplements, ensuring a daily consumption of DF of 21.45 ± 3.86 g/d.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, mice in the CDFC group showed a significant increase in exploratory behavior and time spent in the central area compared to the SD group. Studies have shown that high dietary fiber intake is associated with a reduced prevalence of anxiety [ 36 ]. Dietary fiber can regulate anxiety by promoting the production of short-chain fatty acids that effectively modulate inflammatory factors and neurotransmitter levels [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical functions, including the daily activities of patients with hypertension, have been found to be highly related to the health-related quality of life [ 23 – 25 ]. According to a study on depression in patients with hypertension, a high quality diet was a protective factor for depression in patients with hypertension [ 26 ]. Unhealthy lifestyle habits such as poor quality diets were risk factors for both depression and hypertension [ 16 ], indicating that poor dietary conditions are related to higher degrees of depression in patients with hypertension.…”
Section: Discussionmentioning
confidence: 99%